Internet gaming disorder associated with depression among Thai medical students: A university-based cross-sectional study - Jarurin Pitanupong; Jaruphan Sukhabote; Katti Sathaporn (PLoS ONE, 2025)
Purpose There is evidence that Internet Gaming Disorder (IGD) is strongly related to depression. Hence, this study aimed to investigate the prevalence of IGD among medical students, as well as to examine the association between IGD and depression. Participants and methods From April to July 2024, a cross-sectional study surveyed Thai medical students studying in the first- to sixth-academic year. Participants were recruited using convenience sampling from one Faculty of Medicine and two Medical Education Centers located in southern Thailand. The survey utilized three questionnaires: Demographic and personal inquiry, the Nine-item Internet Gaming Disorder Scale (IGD Scale 9), and the Patient Health Questionnaire-9 (PHQ-9). Data were analyzed using descriptive statistics and logistic regression to assess the prevalence of IGD and its association with depression among the participants. Results The survey of 634 medical students, 54.9% were female, with a median age of 20 years (IQR: 19–22). Notably, 8.4% reported IGD, while 21.6% exhibited symptoms of depression; indicated by a PHQ-9 score of 9 or higher. Of the 114 medical students who were both depressed and engaged in gaming, 26 (4.1%) reported IGD. Statistical analysis indicated significant differences between the IGD and non-IGD groups regarding gender (p = 0.011) and depression (p < 0.001). Furthermore, medical students experiencing depression were about 7.5 times more likely to have IGD (95% CI: 3.8–14.5), indicating a strong correlation between higher PHQ-9 scores and the severity of IGD. Conclusion This study emphasizes the complex relationship between IGD and mental health issues, such as depression, among medical students. Medical schools should establish early detection systems to identify these challenges. By prioritizing prevention strategies for both IGD and depression, medical schools can provide students with the tools to develop healthier coping mechanisms. Encouraging gaming alternatives can significantly enhance their overall well-being and mental health.